TFIIH Operates through an Expanded Proximal Promoter To Fine-Tune c-myc Expression - Weber, Achim (American Society for Microbiology, 2005)
A continuous stream of activating and repressing signals is processed by the transcription complex paused at the promoter of the c-myc proto-oncogene. The general transcription factor IIH (TFIIH) is held at promoters prior to promoter escape and so is well situated to channel the input of activators and repressors to modulate c-myc expression. We have compared cells expressing only a mutated p89 (xeroderma pigmentosum complementation group B [XPB]), the largest TFIIH subunit, with the same cells functionally complemented with the wild-type protein (XPB/wt-p89). Here, we show structural, compositional, and functional differences in transcription complexes between XPB and XPB/wt-89 cells at the native c-myc promoter. Remarkably, although the mean levels of c-Myc are only modestly elevated in XPB compared to those in XPB/wt-p89 cells, the range of expression and the cell-to-cell variation of c-Myc are markedly increased. Our modeling indicates that the data can be explained if TFIIH integrates inputs from multiple signals, regulating transcription at multiple kinetically equivalent steps between initiation and promoter escape. This helps to suppress the intrinsic noise of transcription and to ensure the steady transcriptional output of c-myc necessary for cellular homeostasis.